Resting Behaviour of Zika and Dengue Vector Aedes Aegypti Mosquito in Gia Lai, Viet Nam - Van Nguyen Do; Xuan Quang Nguyen; Hong Quang Huynh; Van Hoang Ho; Thanh Son Tran; Thi Mong Diep Nguyen (My University, 2020)
Resting Behaviour of Zika and Dengue Vector Aedes Aegypti Mosquito in Gia Lai, Viet Nam
Keywords: Aedes Aegypti; Zika & Dengue; Gia Lai